2011
DOI: 10.1007/s00442-011-2149-z
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical patterns and co-occurrence of pathogenic infection across island populations of Berthelot’s pipit (Anthus berthelotii)

Abstract: Pathogens can exert strong selective forces upon host populations. However, before we can make any predictions about the consequences of pathogen-mediated selection, we first need to determine whether patterns of pathogen distribution are consistent over spatiotemporal scales. We used molecular techniques to screen for a variety of blood pathogens (avian malaria, pox and trypanosomes) over a three-year time period across 13 island populations of the Berthelot's pipit (Anthus berthelotii). This species has only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 83 publications
5
90
2
2
Order By: Relevance
“…Two lines of evidence, however, suggest that the dispersal of vagrant silvereyes has little influence on these dynamics. A growing number of studies have demonstrated differences in haemosporidian parasite frequencies between island and mainland populations despite regular arrivals of dispersing avian hosts (Beadell et al, 2007;Spurgin et al, 2012;P erez-Rodr ıguez et al, 2013), and our results suggest that parasite host-specificity could explain this phenomenon. Second, the observed detection probabilities across years for Haemoproteus and Plasmodium lineages in island silvereyes were substantially different from those expected under models that sample from the mainland parasite distribution based on realistic scenarios of vagrant arrivals.…”
Section: Insular Haemosporidian Community Composition and The Role Ofsupporting
confidence: 61%
“…Two lines of evidence, however, suggest that the dispersal of vagrant silvereyes has little influence on these dynamics. A growing number of studies have demonstrated differences in haemosporidian parasite frequencies between island and mainland populations despite regular arrivals of dispersing avian hosts (Beadell et al, 2007;Spurgin et al, 2012;P erez-Rodr ıguez et al, 2013), and our results suggest that parasite host-specificity could explain this phenomenon. Second, the observed detection probabilities across years for Haemoproteus and Plasmodium lineages in island silvereyes were substantially different from those expected under models that sample from the mainland parasite distribution based on realistic scenarios of vagrant arrivals.…”
Section: Insular Haemosporidian Community Composition and The Role Ofsupporting
confidence: 61%
“…() and Spurgin et al. (). Pipits caught on the alpine plateau of El Teide volcano (>2000 m above sea level) were classified as a separate population (Spurgin et al.…”
Section: Methodsmentioning
confidence: 98%
“…We have also shown that these populations are exposed to spatially varying pathogen pressures that are consistent over time (Spurgin et al . ) and that MHC genes are rapidly evolving across the populations as a result of gene conversion and positive selection (Spurgin et al . ).…”
Section: Introductionmentioning
confidence: 99%